2003
DOI: 10.1016/s1567-1356(03)00038-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of clinical and environmental isolates in the Brazilian state Rio Grande do Sul

Abstract: In Brazil, 4.5% of the AIDS-related opportunistic infections are caused by Cryptococcus neoformans. This pathogen is a ubiquitous environmental basidiomycetous encapsulated yeast, commonly found in soil and avian excreta. The present study investigates further the population structure of clinical and environmental C. neoformans isolates from south Brazil. One hundred five clinical and 19 environmental (pigeon excreta and Eucalyptus spp.) isolates from the Brazilian state Rio Grande do Sul were characterized ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
98
2
18

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 49 publications
17
98
2
18
Order By: Relevance
“…grubii, serotype A. This finding is consistent with previous studies showing that the majority of the cases of cryptococcosis in immunocompromised hosts, mainly patients with AIDS, in Brazil as well as worldwide, are caused by serotype A 11,12,39,41 . NISHIKAWA et al serotyped 467 C. neoformans isolates from clinical and environmental sources in Brazil.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…grubii, serotype A. This finding is consistent with previous studies showing that the majority of the cases of cryptococcosis in immunocompromised hosts, mainly patients with AIDS, in Brazil as well as worldwide, are caused by serotype A 11,12,39,41 . NISHIKAWA et al serotyped 467 C. neoformans isolates from clinical and environmental sources in Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…Several molecular typing methods have been used in epidemiological analyses of clinical and/or environmental isolates of C. neoformans, including karyotyping, PCR fingerprinting, random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP) 5,7,8,10,12,16,22,26,37,45 . PCR-fingerprinting using mini (M13) or microsatellite [(GACA) 4 ] specific sequences as single primers and RFLP (PLB1 and URA5 genes) methods have grouped global isolates of C. neoformans into eight major molecular types 32,37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…gattii species complex recovered from the environment was extracted as previously described (22). Serotype was determined using the multiplex PCR described by Ito-Kuwa et al, with some modifications (23).…”
Section: Sample Processingmentioning
confidence: 99%
“…Only a few Brazilian studies have investigated the molecular types of environmental Cryptococcus 1,2,3,22,24,28,35 . The distribution of molecular types using the specific primer M13 shows the predominance of VNI (serotype A) in surveyed regions.…”
mentioning
confidence: 99%
“…The distribution of molecular types using the specific primer M13 shows the predominance of VNI (serotype A) in surveyed regions. It is worthwhile to note the presence of VNIV (serotype D) in eucalypt trees in the deep south of Brazil, a subtropical region 2,28 , and of VGI (C. gattii serotype B) in excreta of psittaciformes in the same region 1 . Study of clinical isolates in São Paulo showed that all of them were serotype A and the majority belonged to the molecular type VNI 22 .…”
mentioning
confidence: 99%